PENGEMBANGAN KAPASITAS KELOMPOK PEREMPUAN TANI DESA BOLA BERBASIS WIRAUSAHA OLAHAN SINGKONG (KAOPI) DI KABUPATEN BUTON SELATAN - Hastuti; Wijaya, Andy Arya Maulana; Maulana, Harry Fajar; Abbas, Fitriani; Sunarli, Wa Ode (Dharma: Jurnal Pengabdian Masyarakat, 2025)
Based on the poverty percentages in South Buton Regency was report in 2021 at 14.62%, which is larges number comes from the women's Community are the most vulnerable to fall into the poverty trap. Bola village located in South Buton Regency is known as a producer of cassava, but it has not been able to maximise the added value for the community. There are exist a Women's Business Group (KWT) Bangun Sejahtera that contibute in processes Cassava into Kaopi Flavour, which is one of the raw materials for local food of the Buton Islands community. This Community Service Programme (PKM) aims to help develop the capacity of business groups as well as women's groups in local resource-based business governance, as well as challenges and opportunities to develop into productive and added-value businesses. This programme is held to be carried out through the observation, training and mentoring, as well as an evaluation to find out the result this program. Approach method used in this PKM is Participatory Rural Appraisal (PRA), which involves KWT as a partner as well as the subject of this activity. The participants in this activity are members of KWT and Bola Village Women's Group with a target of 50 people. The findings of this activity showed an increase in the community's understanding of financial management and digital marketing which reached approximately 83.3%. Nevertheless, this programme still needs to be continued through intensive mentoring and business development in the field of product intellectual property rights and product branding.